(untitled) (Вісник: Міжнародні відносини, 2021)
The marketing strategies are being replaced with the risk-based ones at the background of the high competition level at the consumer goods, increase in the level of the buyers’ requirements for the products, introduction of product standardisation and certification (especially at the European markets), and increase in the level of availability of goods and information on their quality. The article summarises the theoretical framework of the paradigm of risk-based marketing strategies in the context of probable risks due to the spontaneity of marketing actions, the need to continuously monitor the structure of the industry, information on the market and competitive position of the company. The paradigm of the riskbased marketing strategies started to develop in the 1970-1980s of the twentieth century in the context of separation of the main attributes of corporate strategies: planning or spontaneity. The main reasons for development of the risk-based marketing strategies are determined: growth of the current market information that influences the company’s actions, decisions on the product prices in the short term; high market requirements for the quality, costs and speed of delivery of products, growing expectations of customers; need to certify products and introduce standardisation schemes; high level of complexity in managing relations with a large number of suppliers. The paradigm of the risk-based marketing strategies must be considered in the context of ideas of entrepreneurship, marketing and risk as fundamental related economic categories. These concepts are always characterised by innovation and risk subject to the type of consumer market.